PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA TENTANG BANGUN RUANG PADA SISWA KELAS V SDN 1 WALUYOREJO TAHUN AJARAN 2019/2020 - Neni Anggriyaningsih; Wahyudi Wahyudi; Ratna Hidayah (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
Abstract: The research aimed o: (1) describe the steps of Contextual Teaching and Learning (CTL) model, (2) improve mathematics learning outcomes about solid figures, (3) describe obtacle and solution in applying Contextual Teaching and Learning (CTL) model. It was collaborative classroom action research conducted in three cycles and six meetings. The subjects were teacher and 33 students of fifth grade at SDN 1 Waluyorejo. The types of data were qualitative and quantitative. Data collection techniques included observation, interviews, and tests. The data validity used triangulation of techniques and triangulation of sources. Data analysis included data reduction, presentation, and drawing conclusions. The results showed that: (1) the steps in applying the Contextual Teaching and Learning (CTL) model were: (a) the students developed their skills, (b) the students carried out discovery activities, (c) the teacher encouraged the students to ask questions, (d) the students worked in group, (e) the students presented concrete objects, (f) the students made reflection, and (g) the teacher made assessment; (2) the application of Contextual Teaching and Learning (CTL) model improved mathematics learning outcomes about solid figures to the fifth grade students of SDN 1 Waluyorejo in academic year of 2019/2020; (3) the obstacle was that the teacher was difficult to accurately evaluate the contribution of individual student within group work while the solution was that the teacher needed to focus during process of group work.